Designing e-Learning Applications Using the Octalysis Gamification Framework - Fitriana Kadir, Shaifany; Auwal Salisu, Imam (Journal of Information Technology application in Education, Economy, Health and Agriculture, 2024)
In the digital era, information technology has penetrated various aspects of life, including education, with e-learning and gamification becoming increasingly popular approaches. Gamification in e-learning utilizes game mechanics to increase user motivation and participation in digital learning. The Hedonic-Motivation System Adoption Model (HMSAM) is an important evaluation model for assessing the effectiveness of gamification with a focus on hedonic motivations such as satisfaction and engagement. This study aims to explore the application of HMSAM in evaluating gamification-based e-learning applications, as well as understanding the influence of elements such as Epic Meaning, Accomplishment, and Social Influence on user motivation. This evaluation is expected to produce effective strategies to improve the learning experience and maximize the use of e-learning applications. The research methods include a literature study on Design Principles and the Octalysis framework, the development of Android-based mobile applications using Android Studio and Firebase, and application evaluation using HMSAM. The results of the study are expected to provide important contributions to the design of more effective and enjoyable e-learning applications.